Análise da fragilidade ambiental na microbacia do Rio Lajeado Pardo, Frederico Westphalen, RS - Mendonça, Pedro Carvalho de (2024)
This study was carried out in the Lajeado Pardo River basin, located on the border between the municipalities of Frederico Westphalen and Taquaruçu do Sul in the northwest of the state of Rio Grande do Sul. Manuscript 1 addressed the issue of environmental fragility of the studied basin, using the methodology of Ross (1994) adapted from Bonifácio (2013) to determine the potential and emerging environmental fragility of the study area. Through this methodology, it was verified that the potential environmental fragility presents two distinct regions on the map. In relation to emerging environmental fragility, it was possible to perceive that the majority of the analyzed territory was classified as low to moderate degrees of fragility. In order to perform a qualitative and quantitative evaluation of the surface water resources of the Lajeado Pardo River microbasin, samples were collected at three different times at seven sampling points to quantify the concentrations of ammoniacal N, nitrite, nitrate, phosphorus, microbiological and pesticides, using the APHA (1999) methodologies for the physical-chemical parameters, Colilert® (Idexx) for microbiological analysis and for the pesticides Gas Chromatography (GC) and Liquid Chromatography (LC) both coupled to specific detectors. For the physical-chemical and microbiological parameters, it was noticed that they are related to the use and coverage of the land such as agriculture, fertigation, extensive and confined livestock farming, urbanization being the main agents of environmental impacts, causing imbalance and environmental contamination of the Lajeado Pardo River microbasin. For pesticides, the presence of the active ingredients Pirimiphós-methyl, Formothion and Lambda-cyalothrin was verified, which are contaminating the surface waters of the Lajeado Pardo River.